Gaps in the Organization of Emergency Room Care and Services for Women Experiencing Miscarriage: A Multiple Case Study of Four ERs in Quebec - de Montigny, Francine; Verdon, Chantal; Dennie-Filion, Emmanuelle; Gauvreau, Serge (Science of Nursing and Health Practices / Science infirmière et pratiques en santé)

(untitled) (Réseau de recherche en interventions en sciences infirmières du Québec (RRISIQ), 2020)
Introduction: Miscarriage is common, occurring in nearly 20% of pregnancies. Most women experiencing symptoms such as bleeding or abdominal pain in early pregnancy consult emergency services, the front line of care. While research has shown the psychological and physical effects of miscarriage on women, less is known about how emergency services are organized to manage their care. Objective: To describe and analyze the organization of emergency services for women experiencing miscarriage. Methods: A multiple case study was conducted in four emergency rooms in Quebec, Canada, between 2014 and 2015. A reference framework setting out an organized system of action in care adapted to emergency services was used to analyze 198 medical records of women who experienced miscarriage and were treated in these emergency rooms. Results: From the analysis, observations were made regarding the accessibility, responsiveness, and productivity of emergency services, as well as deficiencies in care continuity. While medical treatments generally corresponded to standards, system responsiveness was poor, with long waits that may have added to women’s psychological distress. Gaps were observed in care continuity, effectiveness, and quality, including missing notes in charts, high readmission rates, and lack of referrals to relevant psychosocial and other support services. Discussion and conclusion: Recommendations include developing clinical guidelines, care trajectories, and checklists for nurses’ clinical assessments. As well, early pregnancy assessment clinics are an innovative care delivery model that has proven effective in reducing admissions, shortening hospitalizations, and providing comprehensive support services.